2021
DOI: 10.7554/elife.73430
|View full text |Cite
|
Sign up to set email alerts
|

Experiments from unfinished Registered Reports in the Reproducibility Project: Cancer Biology

Abstract: As part of the Reproducibility Project: Cancer Biology, we published Registered Reports that described how we intended to replicate selected experiments from 29 high-impact preclinical cancer biology papers published between 2010 and 2012. Replication experiments were completed and Replication Studies reporting the results were submitted for 18 papers, of which 17 were accepted and published by eLife with the rejected paper posted as a preprint. Here, we report the status and outcomes obtained for the remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…For 18 of the original papers we were able to implement modifications to complete the proposed experiments resulting in a total of 17 published Replication Studies with the one rejected Replication Study posted as a preprint ( Pelech et al, 2021 ). For the five original papers where we completed some of the experiments the results of the completed replications were reported in an aggregate paper ( Errington et al, 2021a ). In total there were 158 effects with replication outcomes from 50 experiments (effects per experiment: M = 3.2; SD = 2.4; range = 1–13) that came from 23 papers (effects per paper: M = 3.9; SD = 2.8; range = 1–13).…”
Section: Methodsmentioning
confidence: 99%
“…For 18 of the original papers we were able to implement modifications to complete the proposed experiments resulting in a total of 17 published Replication Studies with the one rejected Replication Study posted as a preprint ( Pelech et al, 2021 ). For the five original papers where we completed some of the experiments the results of the completed replications were reported in an aggregate paper ( Errington et al, 2021a ). In total there were 158 effects with replication outcomes from 50 experiments (effects per experiment: M = 3.2; SD = 2.4; range = 1–13) that came from 23 papers (effects per paper: M = 3.9; SD = 2.8; range = 1–13).…”
Section: Methodsmentioning
confidence: 99%
“…The RPCB had two main aims: to provide evidence about replicability in preclinical cancer research, and to identify the factors that influence replicability more generally. Now, seven years later, the final three articles from the project have just been published, and they confirm that there is still considerable scope for improving the reproducibility of preclinical research in cancer biology ( Errington et al, 2021a ; Errington et al, 2021b ; Errington et al, 2021c ).…”
mentioning
confidence: 75%
“…For 18 of the original papers we were able to complete all experiments described in the Registered Report, so for each of these we prepared and submitted a Replication Study that reported the results of the completed experiments. For five of the original papers we were only able to complete some of the experiments described in the Registered Report: in these cases the results of the completed experiments were reported in an aggregate paper ( Errington et al, 2021a ).…”
Section: Challenges During Experiments and Peer Reviewmentioning
confidence: 99%
“…50 experiments from 23 Registered Reports were completed. 17 Replication Studies reporting the results of 41 experiments were published in eLife ; the results of another nine experiments from the six remaining Registered Reports were published in an aggregate paper ( Errington et al, 2021a ). The Replication Studies are listed in column 5, and the number of experiments included in each study is listed in column 6.…”
Section: Introductionmentioning
confidence: 99%